Fundamental patterns of in-store shopper behavior. (July 2017) - Sorensen, Herb; Bogomolova, Svetlana; Anderson, Katherine; Trinh, Giang; Sharp, Anne; Kennedy, Rachel; Page, Bill; Wright, Malcolm
Abstract: This research confirms empirical patterns about in-store behaviors based on a large number of shops and store visits, specifically 654, 000 transactions in 40 supermarkets, hypermarkets, convenience and specialty stores in the USA, UK, China, and Australia. Integrating new data with past findings highlights that: (i) many shopping trips are short; (ii) shoppers typically only cover a small proportion of the store on any trip, and (iii) the heterogeneity of key behavioral measures (store coverage, number of items bought, and trip length) is generalizable across countries, most store formats, and store size. These patterns can help retailers and manufacturers benchmark and predict behavior and provide a base for further theoretical developments.